In vitro degradation and metabolism of sulphur supplemented oat hay by anaerobic fungi from buffalo and cattle - DULAR, R K; SANGWAN, D C (The Indian Journal of Animal Sciences, 2014)
In vitro rumen simulated study was conducted by fermenting oat hay with anaerobic fungi from buffalo and cattle under dietary sulphur levels of 0. 1,0.2,0.3 and 0.4% (on DM basis) for various time intervals. Ruminal disappearances of dry matter, gas production, rumen metabolites and cellulase activity were influenced (P<0.05) by sulphur supplementation as compared to control in both ruminant species and varied between cattle and buffalo. Buffalo (60.8%) excelled (P<0.05) cattle (59.6%) fungi in fermenting DM of oat hay. Maximum (P<0.05) DM degradability was observed at 0.3% level of sulphur in cattle (62.7%) and buffalo (63.0%), which corroborated the pattern on ruminal gas production profile. Rumen nitrogen constituents (total -N and protein-N), TVFA and cellulase activity were maximum (P<0.05) at 0.3% level of sulphur in cattle (115.3, 18.9 mg%, 136.4 meq/I and 475.2 ug sugar/mg protein) and buffalo (118.8, 19.2 mg %, 139.0 meq/I and 465.3 ug sugar/mg protein) barring ammonia-N, which decreased due to sulphur supplementation and minimum (P<0.05) at 0.3% level in cattle (39.4%) and buffalo (38.0 mg%). Of the graded levels of sulphur, 0.3% helped in the maximizing in vitro DM digestion and nitrogen metabolism by anaerobic fungi. Rumen fungi from buffalo enhanced DM degradation and rumen protein-N constituent than cattle fungi.